PENGELOLAAN PETERNAKAN TERPADU PADA KELOMPOK PETERNAK KAMBING MUALAF DI KALIBAWANG KULONPROGO - Lis Noer Aini; Meika Kurnia Puji Dyah Anggraini; Eko Hanudin (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2023)
Kalibawang is one of the hilly areas in Kulonprogo Regency. Most of the people in this area are Muslim, although the number of followers of other religions is also growing. Part of the people in Kalibawang are converts, are a lower until middle class society. The existing economic limitations have made some of the converts formed a group of goat breeders with capital from donors. This goat breeder group has been running for about 1 year and has 6 members, with the number of goats increasing. The problem is the limited knowledge of the members of the farmer group for integrated goat farming system. The solutions offered are 1) providing  training on the manufacture of organic fertilizer from existing goat farm waste; 2) integrated goat farming practices. The results of the assistance carried out, before the training was carried out, all converts did not know how to make organic fertilizer and cultivate goats correctly. After the counseling and mentoring was carried out, farmers began to understand the integrated goat farming technique, and began to put it into practice, both in waste management and in the design of healthier cattle pens.